The North Atlantic Oscillation and sea surface temperature affect loggerhead abundance around the Strait of Gibraltar. - Báez, José Carlos; Bellido López, Juan Jesús; Ferri-Yáñez, Francisco; Castillo, Juan José; Martín, Juan J.; Mons Checa, Jose Luís; Romero-Pacheco, David; Real-Giménez, Raimundo (Institut de Ciències del Mar, CSIC, 2011)
The aim of this study was to explore the possible link between variations in the North Atlantic Oscillation (NAO) and sea surface temperature (SST) and the abundance of loggerhead turtles around the Strait of Gibraltar, using stranding data for the Andalusian coastal area as a proxy for abundance. The annual average SST (from November to October) in the Gulf of Cadiz was negatively associated with the total number of loggerhead strandings each year from November 1997 to October 2006 in the Gulf of Cadiz and the Alboran Sea. The average NAO index was positively associated with the number of strandings in the Gulf of Cadiz in the following year. Prevailing westerly winds during positive NAO phases and the subsequent delayed decrease in SST may lead to turtles from the west Atlantic accumulating in the Gulf of Cadiz and unsuccessfully attempting to return. Secondary causes, such as buoyancy, cold stunning, longline fisheries, net fisheries, debilitated turtle syndrome, and trauma may also increase the number of turtle strandings.
https://v2.sherpa.ac.uk/id/publication/9827
Keywords: Tortugas marinas; Mares y océanos - Temperatura; Gulf of Cadiz; Mediterranean Sea; Global change; Marine migratory species; Sea turtle